Practical chemistry for gcse - Ramsden, Eileen ([S.l.] : Simon & Schuster Education, 1987)
An assessment guide supplementing "Practical Chemistry for GCSE" (also covers Scottish S4-S5 levels) which describes 100 science experiments. Detailed guidance is given to teachers on how to use 30 of them for assessment by each of the six GCSE boards dealing with this chemistry level.
Keywords: chemistry,practical chemistry